International Monetary Fund Annual Report 1986. (Annual Report of the Executive Board; Annual Report of the Executive Board, 1986)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1986. The report highlights that the world economy during 1985 and the early part of 1986 presented a mixed picture. On the positive side, inflation receded further, world output increased at a moderate pace, and interest rates declined significantly. At the same time, the slowdown in industrial countries, particularly in the United States, was sharper than expected, world trade was sluggish, protectionist pressures intensified, and the developing world experienced a setback in its efforts to achieve growth with adjustment.